Community Training in Vermicompost and Vermiwash Production from Organic Waste in Pedakbaru, Bantul, Special Region of Yogyakarta - Permatasari, Irene Putri; Sutanto, Haryati B.; Kisworo, Kisworo (Journal of Innovation and Community Engagement, 2025)
Increasing household food waste in the Special Region of Yogyakarta results from changing consumption patterns and excessive portion sizes. Effective household organic waste management is therefore essential to minimize its environmental impact. This community service activity, carried out by the Faculty of Biotechnology, Duta Wacana Christian University, addressed the problem of household organic waste in Pedakbaru RW07, Karangbendo, Banguntapan, Bantul. Through education that links waste challenges with actionable solutions based on organic waste processing, participants learned to convert kitchen scraps into valuable resources. The training successfully enabled 25 participants to produce vermicompost and vermiwash from household organic waste using repurposed containers, demonstrating a practical and scalable approach to waste reduction. This outcome reflects the value of collaboration between university stakeholders and residents in adopting sustainable, locally adapted waste management practices.